The Development of Computer-Based Islamic Religious Education Module In Class XI Students - Sulaiman Sulaiman; Syntia Adrian Putri (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This study aims to produce a computer-based Islamic Religious Education module that meets the aspects of validity, practicality and effectiveness.The method used in this research is research and development with a design developed by Thiangarajan 4-D models.The research is divided into 4 stages, namely the definition stage, the design stage, the development stage and the dissemination stage.Data sources consisted of qualitative data and quantitative data. Qualitative data in the form of data was obtained through observation and interviews which include comments, criticism, and suggestions. Quantitative data in the form of analysis was collected through the results of student response from questionnaires, practicality questionnaires, validation sheets and learning outcomes tests. The subjects of this research were 32 students of class XI of MIPA at SMAN 1 Sawahlunto.The data were collected throughquestionnaires, observations and tests. The results of the study showed that the computer-based PAI module met the aspects of validity, practicality, and effectiveness where 85% of student learning outcomes tests scored above 75 or in the complete category.